2013
DOI: 10.1021/ef4010253
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Filters in the Formation and Stabilization of Semiquinone Radicals Collected from Cigarette Smoke

Abstract: The fractional pyrolysis of Bright tobacco was performed in nitrogen atmosphere over the temperature range of 240 – 510 °C in a specially constructed, high temperature flow reactor system. Electron paramagnetic resonance (EPR) spectroscopy was used to analyze the free radicals in the initially produced total particular matter (TPM) and in TPM after exposure to ambient air (aging). Different filters have been used to collect TPM from tobacco smoke: cellulosic, cellulose nitrate, cellulose acetate, nylon, Teflon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Specific care must be taken using the filters for collection of radicals. One of our authors has shown the dramatic role of the different types of filters (e.g., cellulosic, cellulose nitrate, cellulose acetate, nylon, Teflon, and Cambridge) to collect PM from tobacco smoke [42]. The collection of the primary radicals (measured immediately after collection of PM on filters) depends significantly on the type of the filter.…”
Section: Samplingmentioning
confidence: 99%
“…Specific care must be taken using the filters for collection of radicals. One of our authors has shown the dramatic role of the different types of filters (e.g., cellulosic, cellulose nitrate, cellulose acetate, nylon, Teflon, and Cambridge) to collect PM from tobacco smoke [42]. The collection of the primary radicals (measured immediately after collection of PM on filters) depends significantly on the type of the filter.…”
Section: Samplingmentioning
confidence: 99%
“…The presence of water deactivates EPFR; EPFR concentration decreases 5× faster at an RH of ~75% than those exposed to less humid conditions [28,30]. pH affects EPFR stability by shifting the type of EPFRs such as those in cigarette smoke [40]. Differences in pH affect the availability of transition metals due to redox reaction, autooxidation, and complexation [41,42].…”
Section: Lifetimes and Factors Affecting The Stability And Persistence Of Epfrsmentioning
confidence: 99%
“…Many organic molecules are EPFR precursors. These classes of organic compounds have been reported to form EPFRs: aromatics [40,43,44] chloroaromatics [2,[45][46][47][48], polycyclic aromatic hydrocarbons (PAHs) [49,50], complex organic polymers [31,51], and microplastics [52]. Another abundant source of EPFR precursors is soil, which contains a vast reservoir of metals and organics [20].…”
Section: Sources and Precursors Of Epfrsmentioning
confidence: 99%
“…CFPs are glass fiber filters able to retain at least 99.9 % of all particles contained in tobacco smoke or e-cig aerosol (Total Particulate Matter or TPM) [7,8], and they are efficient in trapping nicotine at source for both cigarette smoke (at least 99.9%) and e-cig aerosol (> 98%) [9]. In a previous study, we investigated different storing conditions able to guarantee the preservation and stability of the nicotine trapped on CFPs.…”
Section: Introductionmentioning
confidence: 99%